Bacterial Toxins Methods and Protocols - Holst, Otto.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2000)
The interest of investigators across a broad spectrum of scientific dis- plines has been steadily stimulated by the field of bacterial toxin research, an area that makes use of a large variety of biological, chemical, physicochemical, and medically oriented approaches. Researchers studying bacterial toxins need to be acquainted with all these disciplines in order to work effectively in the field. To date, there has been no published collection offering detailed descr- tions of the techniques and methods needed by researchers operating across the field’sdiverse areas. The present volume Bacterial Toxins: Methods and Pro- cols, is intended to fill this gap. Bacterial Toxins: Methods and Protocols consists of two sections: one on protein toxins (15 chapters) and one on endotoxins (5 chapters). Each s- tion is introduced by an overview article (Chapters 1 and 16). The protocols collected represent state-of-the-art techniques that each have high impact on future bacterial toxin research. All methods are described by authors who have regularly been using the protocol in their own laboratories. Included in each chapter is a brief introduction to the method being described.
Bacterial Protein Toxins -- Purification of Clostridium botulinum Type A Neurotoxin -- Shiga Toxins -- Isolation and Detection of Microcystins and Nodularins, Cyanobacterial Peptide Hepatotoxins -- Genetic Construction, Expression, and Characterization of Diphtheria Toxin-Based Growth Factor Fusion Proteins -- Structure-Function Analysis of Cysteine-Engineered Entomopathogenic Toxins -- Use of Fourier-Transformed Infrared Spectroscopy for Secondary Structure Determination of Staphylococcal Pore-Forming Toxins -- The Use of Fluorescence Resonance Energy Transfer to Detect Conformational Changes in Protein Toxins -- Site-Directed Spin Labeling of Proteins -- Characterization of Molecular Properties of Pore-Forming Toxins with Planar Lipid Bilayers -- Determination of Affinity and Kinetic Rate Constants Using Surface Plasmon Resonance -- ADP-Ribosylation of ?-Gi Proteins by Pertussis Toxin -- Phage Libraries for Generation of Anti-Botulinum scFv Antibodies -- T-Cell Cytotoxicity Assays for Studying the Functional Interaction Between the Superantigen Staphylococcal Enterotoxin A and T-Cell Receptors -- In Vitro Physiological Studies on Clostridial Neurotoxins -- The Biology of Endotoxin -- Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry of Lipopolysaccharides -- Applications of Combined Capillary Electrophoresis-Electrospray Mass Spectrometry in the Characterization of Short-Chain Lipopolysaccharides -- Deacylation of Lipopolysaccharides and Isolation of Oligosaccharide Phosphates -- Electrophysiological Measurements on Reconstituted Outer Membranes.
Keywords: Microbiology; Microbiology